Multi-layer modified vermiculite material for adsorbing PFOA (perfluorooctanoic acid) and preparation method thereof

By performing multi-layer modification of vermiculite, multi-layer modified vermiculite material is prepared, which solves the persistence and bioaccumulative problems of PFOA in the environment, and achieves the effect of efficient adsorption and removal of PFOA.

CN119746805AInactive Publication Date: 2025-04-04EAST CHINA UNIV OF SCI & TECH +1

Patent Information

Application Number
CN202411886806.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Perfluorooctanoic acid (PFOA) has extremely strong durability and bioaccumulative properties in the environment, which is difficult to degrade, resulting in ecological environment and human health risks.

Method used

Multi-layer modified vermiculite material is prepared by performing multi-layer modification, including sodiumization, organic active modification and deep modification. The surface of the material is rich in positive charge and hydrophobicity, and can efficiently adsorb negatively charged PFOA.

Benefits of technology

It significantly improves the adsorption performance of PFOA, achieves efficient removal of PFOA in water treatment, and provides a continuous and efficient solution for the removal of perfluoro compounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746805A_ABST
    Figure CN119746805A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-layer modified vermiculite material for adsorbing PFOA (perfluorooctanoic acid) and a preparation method of the multi-layer modified vermiculite material, and belongs to the technical field of functional materials for environmental restoration. According to the preparation method disclosed by the invention, vermiculite is modified by sequentially using sodium chloride, sodium trifluoroacetate and cetyltrimethylammonium bromide (CTAB) to obtain the multi-layer modified vermiculite material, and the material can efficiently adsorb and remove PFOA.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental remediation functional materials, and in particular relates to a multi-layer modified vermiculite material for adsorbing PFOA and a preparation method thereof. Background Art

[0002] Perfluorooctanoic acid (PFOA) is a perfluorinated compound widely used in industrial production. Due to the highly stable C-F bonds in its molecular structure, PFOA is extremely persistent and bioaccumulative in the environment, making it difficult to degrade naturally. This property poses a high risk to the ecological environment and has adverse effects on human health.

[0003] Vermiculite (VT) is a layered silicate material with a large specific surface area, adsorption, and ion exchange properties, making it widely used in water treatment and pollutant adsorption. Based on the principles of "electrostatic interaction" and "fluorine-fluorine like compatibility," VT is modified to improve its surface hydrophilicity and interlayer environment, enabling efficient adsorption of organic pollutants. It holds great potential for development and application in the treatment of emerging pollutants such as perfluorinated compounds. Summary of the Invention

[0004] In order to solve the above problems in the prior art, the present invention proposes a multi-layer modified vermiculite material for adsorbing PFOA and a preparation method thereof.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A preparation method of a multi-level modified vermiculite material comprises the following steps: modifying vermiculite with sodium chloride, sodium trifluoroacetate and cetyltrimethylammonium bromide (CTAB) in sequence to obtain the multi-level modified vermiculite material, namely, sodium chloride is used to sodiumize the vermiculite, sodium trifluoroacetate is used to organically modify the obtained sodium-based modified vermiculite, and cetyltrimethylammonium bromide is used to deeply modify the obtained fluorine-modified sodium-based vermiculite to obtain the multi-level modified vermiculite material.

[0007] The present invention uses vermiculite with a layered structure as the base material. First, its ion exchange capacity is improved through sodium-based treatment. Then, sodium trifluoroacetate is used to modify the sodium-based vermiculite to be organically active. Active groups are introduced during the reaction process, thereby increasing the material's adsorption capacity for organic matter. Finally, the modified vermiculite material is further modified using hexadecyltrimethylammonium bromide. The hydrophobic groups of hexadecyltrimethylammonium bromide can enter the interlayer structure of the vermiculite and make it rich in positive charge, further enhancing its adsorption efficiency for hydrophobic and negatively charged pollutants. The resulting multi-layered modified vermiculite material is used in water treatment and can efficiently adsorb PFOA. This material has a large specific surface area, strong hydrophobicity, and rich positive charge, which significantly improves the adsorption performance for PFOA and provides a continuous and efficient solution for the removal of perfluorinated compounds.

[0008] Furthermore, the preparation method specifically comprises the following steps:

[0009] (1) Sodiumization of vermiculite in a sodium chloride aqueous solution to obtain a sodium-modified vermiculite (Na-VT) precursor;

[0010] (2) washing, drying, grinding and screening the sodium-modified vermiculite precursor in sequence, roasting, and grinding and screening again to obtain sodium-modified vermiculite (Na-VT);

[0011] (3) using a sodium trifluoroacetate aqueous solution to perform organic active modification on the sodium-modified vermiculite to obtain a fluorine-modified sodium-based vermiculite (F-Na-VT) precursor;

[0012] (4) washing, drying, grinding and screening the fluorine-modified sodium vermiculite precursor in sequence to obtain fluorine-modified sodium vermiculite (F-Na-VT);

[0013] (5) using a hexadecyltrimethylammonium bromide aqueous solution to deeply modify the fluorine-modified sodium vermiculite to obtain a multi-level modified sodium vermiculite (CTAB-F-Na-VT) precursor;

[0014] (6) The multi-layer modified sodium-based vermiculite precursor is washed, dried, ground and sieved in sequence to obtain a multi-layer modified vermiculite (CTAB-F-Na-VT) material.

[0015] Furthermore, in step (1),

[0016] The specific process of the sodium modification is as follows: dissolving sodium chloride in water, then dispersing vermiculite in the sodium chloride aqueous solution, ultrasonically treating at 20-25° C. for 30-40 minutes, and then shaking for 8-10 hours. The resulting precipitate is the sodium-modified vermiculite precursor; and / or

[0017] The usage ratio of the vermiculite, sodium chloride and water is (20-25) g: (7.0-7.5) g: (200-250) mL.

[0018] Furthermore, in step (2),

[0019] The specific process of the calcination is: the temperature of the muffle furnace is increased to 600-800° C. at a heating rate of 10-20° C. / min, and the calcination is carried out at this temperature for 2-3 hours.

[0020] Furthermore, in step (3),

[0021] The specific process of the organic active modification is: dissolving sodium trifluoroacetate in water, then dispersing the sodium-modified vermiculite in the sodium trifluoroacetate aqueous solution, heating in a water bath, and the resulting precipitate is the fluorine-modified sodium-based vermiculite precursor; and / or

[0022] The parameters of the water bath heating are: temperature 60-65°C, time 8-12h; and / or

[0023] The usage ratio of the sodium-based modified vermiculite, sodium trifluoroacetate and water is (8-10) g: (3.4-4.4) g: (50-100) mL.

[0024] Furthermore, in step (5),

[0025] The specific process of the deep-level modification is: dissolving hexadecyltrimethylammonium bromide in water, then dispersing the fluorine-modified sodium vermiculite in the hexadecyltrimethylammonium bromide aqueous solution, heating in a water bath, and the resulting precipitate is the multi-level modified sodium vermiculite precursor; and / or

[0026] The parameters of the water bath heating are: temperature 60-65°C, time 8-12h; and / or

[0027] The usage ratio of the fluorine-modified sodium vermiculite, hexadecyltrimethylammonium bromide and water is (4-6) g: (4.5-5.5) g: (50-100) mL.

[0028] Further, in step (2), step (4) and step (6),

[0029] The specific process of the washing is: washing with deionized water and anhydrous ethanol for 2-5 times respectively; and / or

[0030] The drying parameters are: temperature 60-80°C, time 12-24h; and / or

[0031] The grinding and sieving refers to grinding until the powder passes through a 200-mesh sieve.

[0032] The present invention also provides a multi-layer modified vermiculite material prepared by the above preparation method.

[0033] The present invention also provides an application of the multi-layer modified vermiculite material as a material for adsorbing perfluorooctanoic acid.

[0034] Compared with the prior art, the present invention has the following advantages and technical effects:

[0035] The present invention synthesizes multi-layered modified vermiculite through a multi-step process. Initially, the raw vermiculite is sodium-modified at room temperature, followed by further modification through a mixing reaction, ultimately yielding the multi-layered modified vermiculite. This reaction operates under mild conditions, does not involve the use of toxic or hazardous raw materials, and produces a highly efficient, stable, and environmentally friendly adsorbent material.

[0036] The surface of the multi-layered modified vermiculite material prepared based on the present invention not only carries abundant positive charges, but also its adsorption selectivity is effectively improved after CF modification, thereby achieving efficient adsorption and removal of organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The accompanying drawings, which constitute part of this application, are intended to provide a further understanding of this application. The exemplary embodiments and descriptions of this application are intended to explain this application and do not constitute an improper limitation on this application. In the accompanying drawings:

[0038] Figure 1 The scanning electron microscopy results of VT, F-Na-VT and CTAB-F-Na-VT in Example 1 of the present invention are shown;

[0039] Figure 2 The following are the Fourier transform infrared spectroscopy characterization results of VT, Na-VT, F-Na-VT and CTAB-F-Na-VT in Example 1 of the present invention;

[0040] Figure 3 Zeta potential analysis results of VT, Na-VT and CTAB-F-Na-VT in Example 1 of the present invention;

[0041] Figure 4 This is a diagram verifying the effect of VT and CTAB-F-Na-VT in removing perfluorooctanoic acid (PFOA) by adsorption in Example 1 of the present invention;

[0042] Figure 5 This is a verification diagram of the adsorption removal of perfluorooctanoic acid by VT, Na-VT, F-Na-VT, CTAB-F-Na-VT in Example 1 of the present invention and CTAB-Na-VT in Comparative Example 3, as well as the adsorption removal of phenol by CTAB-F-Na-VT in Example 1. DETAILED DESCRIPTION

[0043] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0044] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any intermediate value within a stated value or stated range and any other stated value or intermediate value within the stated range is also encompassed by the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.

[0045] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.

[0046] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be illustrative only.

[0047] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0048] The present invention provides a method for preparing a multi-layer modified vermiculite material, comprising the following steps:

[0049] (1) dissolving a certain amount of NaCl in a certain volume of ultrapure water at a certain temperature, and uniformly dispersing a certain amount of vermiculite (VT) in the NaCl solution to obtain a reaction mixture;

[0050] (2) the mixed solution in step (1) is ultrasonically vibrated at a certain temperature for a certain period of time, and the resulting precipitate is a sodium-modified vermiculite (Na-VT) precursor;

[0051] (3) washing, drying, grinding and sieving the Na-VT precursor obtained in step (2), calcining, and grinding and sieving again to obtain Na-VT;

[0052] (4) dissolving a certain amount of sodium trifluoroacetate in a certain volume of ultrapure water at a certain temperature, and uniformly dispersing a certain amount of Na-VT obtained in step (3) in the sodium trifluoroacetate solution to obtain a reaction mixture;

[0053] (5) heating the mixed solution in step (4) in a water bath for a certain period of time, and the resulting precipitate is a fluorine-modified sodium vermiculite (F-Na-VT) precursor;

[0054] (6) washing, drying, grinding and sieving the F-Na-VT precursor in step (5) to obtain F-Na-VT;

[0055] (7) dissolving a certain amount of cetyltrimethylammonium bromide (CTAB) in a certain volume of ultrapure water, and uniformly dispersing a certain amount of F-Na-VT obtained in step (6) in the CTAB solution to obtain a reaction mixture;

[0056] (8) heating the mixed solution in step (7) in a water bath for a certain period of time, and the resulting precipitate is a multi-layer modified sodium vermiculite (CTAB-F-Na-VT) precursor;

[0057] (9) The CTAB-F-Na-VT precursor in step (8) is washed, dried, ground and sieved to obtain a CTAB-F-Na-VT adsorption material.

[0058] In some preferred embodiments of the present invention, in step (1), the mass of NaCl is 7.0-7.5 g, the volume of ultrapure water is 200-250 mL, the mass of VT is 20-25 g, and the temperature is 20-25° C. That is, the ratio of vermiculite, sodium chloride, and water is (20-25) g: (7.0-7.5) g: (200-250) mL. The target product can be obtained by satisfying these conditions. For example, in the following embodiments of the present invention, the effect data verification is performed using a ratio of vermiculite, sodium chloride, and water of 25 g: 7.3 g: 250 mL and a temperature of 25° C.

[0059] In some preferred embodiments of the present invention, in step (2), the temperature is 20-25°C, the ultrasonic time is 30-40 minutes, and the oscillation time is 8-10 hours. The target product can be obtained by satisfying these conditions. For example, the following examples of the present invention use a temperature of 25°C, an ultrasonic time of 35 minutes, and an oscillation time of 9 hours as an example for effect data verification.

[0060] In some preferred embodiments of the present invention, in step (3), the calcination is performed by heating the temperature in a muffle furnace to 600-800°C at a rate of 10-20°C / min for 2-3 hours. The target product can be obtained by satisfying this condition. For example, in the following embodiments of the present invention, the effect data is verified by heating the temperature in a muffle furnace to 750°C at a rate of 10°C / min for 2 hours.

[0061] In some preferred embodiments of the present invention, in step (4), the mass of the sodium trifluoroacetate is 3.4-4.4 g, the volume of ultrapure water is 50-100 mL, the mass of Na-VT is 8-10 g, and the temperature is 20-25° C. That is, the dosage ratio of the sodium-modified vermiculite, sodium trifluoroacetate, and water is (8-10) g: (3.4-4.4) g: (50-100) mL. The target product can be obtained by satisfying these conditions. For example, in the following examples of the present invention, the dosage ratio of the sodium-modified vermiculite, sodium trifluoroacetate, and water is 8 g: 3.4 g: 50 mL and the temperature is 25° C. as an example for effect data verification.

[0062] In some preferred embodiments of the present invention, in step (5), the water bath temperature is 60-65°C and the water bath heating time is 8-12 hours. The target product can be obtained by satisfying these conditions. For example, the following examples of the present invention use a water bath temperature of 65°C and a water bath heating time of 8 hours as an example for effect data verification.

[0063] In some preferred embodiments of the present invention, in step (7), the mass of the CTAB is 4.5-5.5 g, the volume of ultrapure water is 50-100 mL, the mass of the F-Na-VT is 4-6 g, and the temperature is 20-25° C. That is, the ratio of the fluorine-modified sodium vermiculite, hexadecyltrimethylammonium bromide, and water is (4-6) g: (4.5-5.5) g: (50-100) mL. The target product can be obtained by satisfying these conditions. For example, in the following examples of the present invention, the effect data verification is performed using the ratio of fluorine-modified sodium vermiculite, hexadecyltrimethylammonium bromide, and water being 4 g: 4.6 g: 50 mL and the temperature being 25° C.

[0064] In some preferred embodiments of the present invention, in step (8), the water bath temperature is 60-65°C. The water bath heating time is 8-12 hours. The target product can be obtained by satisfying these conditions. For example, the following examples of the present invention use a water bath temperature of 65°C and a water bath heating time of 8 hours as an example for effect data verification.

[0065] In some preferred embodiments of the present invention, in step (3), step (6), and step (9),

[0066] The washing is performed by washing with deionized water and anhydrous ethanol 2-5 times respectively; the target product can be obtained if this condition is met. For example, in the following embodiments of the present invention, washing with deionized water and anhydrous ethanol 3 times respectively is used as an example to verify the effect data.

[0067] The drying temperature is 60-80°C and the drying time is 12-24h. The target product can be obtained by satisfying the above conditions. For example, the following embodiments of the present invention take the drying temperature of 70°C and the drying time of 24h as an example to verify the effect data.

[0068] The grinding and sieving refers to grinding until the powder passes through a 200-mesh sieve.

[0069] Unless otherwise specified, the "room temperature" in the present invention refers to 20-25°C.

[0070] The raw materials used in the present invention are all purchased from the market.

[0071] The technical solution of the present invention is further illustrated by the following examples.

[0072] Example 1

[0073] Preparation of a multi-layer modified vermiculite material (CTAB-F-Na-VT) for adsorption of PFOA:

[0074] 1) Dissolve 7.3 g of NaCl in 250 mL of ultrapure water at 25°C, and evenly disperse 25 g of VT in the NaCl solution to obtain a reaction mixture;

[0075] 2) ultrasonicating the reaction mixture of step 1) at 25° C. for 35 minutes and then shaking for 9 hours to obtain a precipitate;

[0076] 3) The precipitate obtained in step 2) was washed three times with deionized water and anhydrous ethanol, respectively, and vacuum dried at 70° C. for 24 h; ground through a 200-mesh sieve, and then calcined in a muffle furnace at a rate of 10° C. / min to 750° C. for 2 h, and ground again through a 200-mesh sieve to obtain Na-VT;

[0077] 4) Dissolve 3.4 g of sodium trifluoroacetate in 50 mL of ultrapure water at 25° C., and evenly disperse 8 g of Na-VT prepared in step 3) in the sodium trifluoroacetate solution to obtain a reaction mixture;

[0078] 5) stirring the reaction mixture of step 4) in a water bath at 65° C. for 8 h to obtain a precipitate;

[0079] 6) washing the precipitate obtained in step 5) with deionized water and anhydrous ethanol three times respectively, drying under vacuum at 70° C. for 24 h, and grinding through a 200-mesh sieve to obtain F-Na-VT;

[0080] 7) Dissolve 4.6 g of CTAB in 50 mL of ultrapure water at 25° C., and evenly disperse 4 g of the F-Na-VT prepared in step 7) in the CTAB solution to obtain a reaction mixture;

[0081] 8) Stirring the reaction mixture from step 7) in a water bath at 65° C. for 8 h to obtain a precipitate;

[0082] 9) The precipitate obtained in step 8) was washed three times with deionized water and anhydrous ethanol, respectively, dried under vacuum at 70° C. for 24 h, and ground through a 200-mesh sieve to obtain CTAB-F-Na-VT.

[0083] The materials prepared in Example 1 were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy and Zeta potential analysis. Figure 1-3 shown.

[0084] Depend on Figure 1 It can be seen that the microstructure of the prepared multi-layer modified vermiculite material presents a lamellar structure, and C and F are evenly distributed and coexist on the surface, indicating that the material has been successfully synthesized.

[0085] Depend on Figure 2 It can be seen that the Fourier transform infrared spectrum of the prepared multi-layer modified vermiculite material is at 2923.3 cm -1 and 2853.6cm -1 Obvious vibration peaks appeared, proving the successful modification of CTAB.

[0086] Depend on Figure 3 It can be seen that the surface of CTAB-F-Na-VT is positively charged, so it is easy to adsorb negatively charged PFOA.

[0087] Application Example 1

[0088] PFOA in water was removed by adsorption. The specific steps were as follows: 100 mL of a 10 mg / L PFOA solution was added to a conical flask, and 1.0 g of CTAB-F-Na-VT prepared in Example 1 was added to the system. 1 mL of the reaction solution was collected at the set sampling time (30 min), filtered through a nylon syringe filter, and quickly poured into a brown vial containing 1 mL of methanol solution. The PFOA concentration was detected after shaking for 1 min.

[0089] Test results ( Figure 4 ) showed that CTAB-F-Na-VT could effectively adsorb and remove PFOA, and the adsorption removal rate of PFOA was as high as 95.8% within 120 min.

[0090] Comparative Example 1

[0091] Same as Example 1, except that steps 4) to 7) are omitted.

[0092] The obtained adsorption material was subjected to the same adsorption experiment as in Example 1. The results showed that the removal rate of PFOA within 120 minutes was 5.91%. The reason was that the surface of Na-VT was rich in negative charge and hydrophilicity, and therefore repelled the negatively charged PFOA.

[0093] Comparative Example 2

[0094] Same as Example 1, except that step 7) is omitted.

[0095] The obtained adsorption material was subjected to the same adsorption experiment as in Example 1. The results showed that the removal rate of PFOA within 120 minutes was 59.9%. The reason was that after being modified with trifluoroacetic acid, F-Na-VT achieved the adsorption of PFOA based on the "fluorine-fluorine like dissolves like" theory.

[0096] Comparative Example 3

[0097] The same as Example 1, except that steps 4) to 6) are omitted, and the Na-VT obtained in step 3) is directly subjected to the operation of step 7).

[0098] The obtained adsorption material was subjected to the same adsorption experiment as in Example 1. The results showed that the removal rate of PFOA within 120 minutes was 69.8%. After modification with a cationic surfactant, the surface of CTAB-Na-VT had abundant positive charges, and the adsorption of PFOA was achieved through electrostatic and hydrophobic interactions.

[0099] Comparative Application Example 1

[0100] Same as Application Example 1, except that 100 mL of 10 mg / L PFOA solution is replaced with 100 mL of 10 mg / L phenol solution.

[0101] The adsorption material obtained was subjected to the same adsorption experiment as in Example 1. The results showed that the adsorption removal rate of phenol within 120 minutes was 56.4%. Due to the hydrophobic effect and the positive charge on the surface of the adsorbent after CTAB modification, it also had a certain removal effect on phenol, but the effect was not as good as that of Application Example 1 (see Figure 5 ).

[0102] The above are merely preferred embodiments of the present application, but the scope of protection of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in this application should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be based on the scope of protection of the claims.

Claims

1. A method for preparing a multi-layer modified vermiculite material, characterized in that: Vermiculite is modified by using sodium chloride, sodium trifluoroacetate and hexadecyltrimethylammonium bromide in sequence to obtain a multi-layered modified vermiculite material.

2. The method for preparing the multi-level modified vermiculite material according to claim 1, characterized in that: The preparation method specifically comprises the following steps: (1) sodiumizing vermiculite in a sodium chloride aqueous solution to obtain a sodium-modified vermiculite precursor; (2) washing, drying, grinding and screening, roasting, and grinding and screening again the sodium-based modified vermiculite precursor in sequence to obtain sodium-based modified vermiculite; (3) using a sodium trifluoroacetate aqueous solution to perform organic active modification on the sodium-modified vermiculite to obtain a fluorine-modified sodium-based vermiculite precursor; (4) washing, drying, grinding and screening the fluorine-modified sodium vermiculite precursor in sequence to obtain fluorine-modified sodium vermiculite; (5) using a hexadecyltrimethylammonium bromide aqueous solution to perform deep modification on the fluorine-modified sodium vermiculite to obtain a multi-level modified sodium vermiculite precursor; (6) The multi-layer modified sodium-based vermiculite precursor is washed, dried, ground and sieved in sequence to obtain a multi-layer modified vermiculite material.

3. The method for preparing the multi-level modified vermiculite material according to claim 2, characterized in that: In step (1), The specific process of the sodium modification is: dissolving sodium chloride in water, then dispersing vermiculite in the sodium chloride aqueous solution, ultrasonically treating at 20-25° C. for 30-40 minutes, and then shaking for 8-10 hours, and the resulting precipitate is the sodium-based modified vermiculite precursor; and / or The usage ratio of the vermiculite, sodium chloride and water is (20-25) g: (7.0-7.5) g: (200-250) mL.

4. The method for preparing the multi-level modified vermiculite material according to claim 2, characterized in that: In step (2), The specific process of the calcination is: the temperature of the muffle furnace is increased to 600-800° C. at a heating rate of 10-20° C. / min, and the calcination is carried out at this temperature for 2-3 hours.

5. The method for preparing the multi-level modified vermiculite material according to claim 2, characterized in that: In step (3), The specific process of the organic active modification is: dissolving sodium trifluoroacetate in water, then dispersing the sodium-modified vermiculite in the sodium trifluoroacetate aqueous solution, heating in a water bath, and the resulting precipitate is the fluorine-modified sodium-based vermiculite precursor; The parameters of the water bath heating are: temperature 60-65°C, time 8-12h; and / or The dosage ratio of the sodium-based modified vermiculite, sodium trifluoroacetate and water is (8-10) g: (3.4-4.4) g: (50-100) mL.

6. The method for preparing the multi-level modified vermiculite material according to claim 2, characterized in that: In step (5), The specific process of the deep-level modification is as follows: dissolving hexadecyltrimethylammonium bromide in water, then dispersing the fluorine-modified sodium-based vermiculite in the hexadecyltrimethylammonium bromide aqueous solution, heating in a water bath, and the resulting precipitate is the multi-level modified sodium-based vermiculite precursor; The parameters of the water bath heating are: temperature 60-65°C, time 8-12h; and / or The usage ratio of the fluorine-modified sodium vermiculite, hexadecyltrimethylammonium bromide and water is (4-6) g: (4.5-5.5) g: (50-100) mL.

7. The method for preparing the multi-layer modified vermiculite material according to claim 2, characterized in that: In step (2), step (4) and step (6), The specific process of washing is: washing with deionized water and anhydrous ethanol for 2-5 times respectively; and / or The drying parameters are: temperature 60-80°C, time 12-24h; and / or The grinding and sieving refers to grinding until the powder passes through a 200-mesh sieve.

8. A multi-layered modified vermiculite material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the multi-layer modified vermiculite material as claimed in claim 8 as a material for adsorbing perfluorooctanoic acid.

Citation Information

Patent Citations

  • Method for efficiently degrading perfluorinated compounds (PFCs)

    CN105536198A

  • Magnetic fluorinated adsorbent for selective adsorption of PFOS, preparation method and application thereof

    CN106390933A

  • Method for rapidly removing perfluoro / polyfluoro compounds in environmental water

    CN111252859A

  • Vermiculite nanosheet, preparation method and production system thereof and vermiculite nanosheet heat stabilizer

    CN116715248A

  • Degradation agent of perfluorinated compound and application

    CN117619352A

Cited By

  • Modified vermiculite-loaded cubic cobalt-manganese spinel material and preparation method thereof

    CN120361953A

  • A modified vermiculite-loaded cubic cobalt-manganese spinel material and its preparation method

    CN120361953B

  • Flame-retardant waterproof fabric for bags and suitcases and preparation method of flame-retardant waterproof fabric

    CN120649289A